Refractive index and vapor-liquid equilibrium data for the binary systems of anisole with xylene isomers at 93.13 kPa - Yadav, Satyajeet S.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2018)
Phase equilibrium behavior of binary systems of anisole with xylene isomers was analyzed experimentally. An apparatus which establishes equilibrium conditions through continuous circulation of equilibrium vapor condensate and equilibrium liquid was used. Experimental data comprising refractive indices of binary mixtures, equilibrium compositions of vapor and liquid, and equilibrium temperature are reported for all binary systems. Thermodynamic consistency of vapor-liquid equilibrium data was established for using the Herington, Van Ness and absolute mean deviation tests. Interaction parameters of activity coefficient models, Wilson, nonrandom two liquid, and universal quasichemical, which are important for accounting nonideal behavior in process modeling, are also estimated through regression of the respective binary VLE data. Although VLE data shows that binary systems are nonazeotropic in nature, a pinch in the T-x,y plot indicates that separation of all binary system using distillation may need a significant number of stages.

Reduction of carbon dioxide to dimethylformamide using ruthenium doped Mg/Al hydrotalcites under supercritical conditions - Chaudhary, Sagar D.; Rahatade, Shardul S.; Joshi, Sunil S.; Mali, Nilesh A. (Journal of CO2 Utilization, 2022)
The utilization of carbon dioxide is one of the developing areas due to its significant contribution to global warming. Reducing carbon dioxide (CO2) to formic acid and its derivatives has gained importance because of its thermodynamic limitations and high industrial demand. In this article, we report the synthesis of dime-thylformamide (DMF) using ruthenium doped Mg/Al calcined hydrotalcite by CO2 hydrogenation in the presence of dimethylamine (DMA). At optimized conditions, complete conversion of dimethylamine was achieved with more than 92% product yield at 170 degrees C and 13 MPa pressure with a reaction time of 6 h. Key catalyst properties were determined using X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), CO2-temper-ature programmed desorption (TPD), H-2 temperature-programmed reduction (TPR) and Fourier transform infrared (FTIR). The determination of surface morphology was carried out using field emission scanning electron microscope (FE-SEM) and high-resolution transmission electron microscopy (HR-TEM). At the same time, the chemical composition was verified by energy-dispersive X-ray (EDS). In addition, kinetic modeling is performed using the two site Langmuir-Hinshelwood-Hougen-Watson model. The regressed kinetic parameters gave an appropriate fit with experimental concentration values and activation energy is calculated as 413 kJ/mol K-1.
Keywords: Dimethylformamide; Hydrogenation; hydrotalcite; Langmuir-Hinshelwood-Hougen-Watson model; Supercritical carbon dioxide

Reusable and efficient polystyrene immobilized ionic liquid catalyst for batch and flow methylation of hydroquinone - Bhongale, V. Priyanka; Joshi, Sunil S.; Mali, Nilesh A. (Catalysis Letters, 2022)
An environmentally benign process for synthesizing 4-methoxyphenol through methylation of hydroquinone using polystyrene immobilized Bronsted acidic ionic liquid is presented. The catalyst has been characterized by several techniques, such as solid-state NMR, FTIR, and XRD. The morphological properties were analyzed through SEM and TEM analysis. The elemental analysis was performed using EDS and XPS techniques. The catalyst was thermally stable up to 603 K, which was confirmed by TGA. The chemical interaction between ionic liquid and polystyrene was confirmed by measuring the glass transition temperature of pure polystyrene and catalyst. The BET analysis was performed to estimate the catalyst's surface area, pore size, and pore volume. The recyclability of the proposed new catalyst was established up to five recycle runs in the batch mode. In addition, continuous flow experiments were conducted to test the catalytic activity in terms of catalyst life span and showed excellent stability up to 20 h. The rapid separation, long-term stability, and efficient recycling of synthesized polymeric catalysts make an excellent alternative to the commonly used homogeneous catalysts for selective O-methylation of hydroquinone reaction. The newly developed continuous process for synthesizing 4-methoxyphenol with 100% selectivity suggests good opportunities to reduce energy consumption, which designates a cost-effective process. [GRAPHICS] .
Keywords: 4-Methoxyphenol; Hydroquinone; O-methylation; Polystyrene immobilized ionic liquid